2021
DOI: 10.1177/00111287211046520
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mismatch, Race and Ethnicity, and Unemployment: Implications for Interventions With Women on Probation and Parole

Abstract: For 312 women on probation and parole, we used mediation and conditional process analyses to examine the indirect effect of minority racial/ethnic status on unemployment through spatial mismatch between women’s place of residence and the location of available jobs. Consistent with the spatial mismatch hypothesis, employment opportunities per capita within 2 miles of women’s census tract of residence mediated the relationship between minority status and unemployment. The connection of spatial mismatch to unempl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
3
10
0
Order By: Relevance
“…Showing further disadvantage, Black women were especially likely to note that criminal convictions barred them from certain types of employment. These findings are consistent with prior research showing the greater difficulty that Black system-involved people face because of either discrimination by potential employers or lack of employment opportunities near their residences (Decker et al, 2015; Dodge & Pogrebin, 2001; Harding et al, 2013; Pager, 2003; Richie, 2001; Roddy et al, 2022). Programmatic attention should be paid to assisting system-involved Black women to navigate race-related employment challenges.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Showing further disadvantage, Black women were especially likely to note that criminal convictions barred them from certain types of employment. These findings are consistent with prior research showing the greater difficulty that Black system-involved people face because of either discrimination by potential employers or lack of employment opportunities near their residences (Decker et al, 2015; Dodge & Pogrebin, 2001; Harding et al, 2013; Pager, 2003; Richie, 2001; Roddy et al, 2022). Programmatic attention should be paid to assisting system-involved Black women to navigate race-related employment challenges.…”
Section: Discussionsupporting
confidence: 91%
“…Black women with increasing financial need stood out from the three other groupings by virtue of the low proportion who mentioned securing a new job (see Table 2 for racial group comparisons). The small sample makes this finding only suggestive, but it is consistent with literature showing race increases difficulty for system-involved women to find work (Cobbina, 2009; Roddy et al, 2022).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Women reported that transportation difficulties often shape the nature of the jobs they take as well as the methods they use to search for work. As emphasized in prior literature (see Roddy et al, 2022), employment opportunities located in women's area of residence are of unique consequence for women that are system-involved, especially for those with low transportation access.…”
Section: Strategies To Navigate Barriersmentioning
confidence: 99%
“…Women’s pathways are frequently rooted in dysfunctional intimate relationships, abuse/trauma/victimization, and low social and human capital (Brennan et al, 2012; Daly, 1992; Gehring, 2016; Salisbury & Van Voorhis, 2009). Furthermore, intersectional interventions for women of color on supervision are a crucial part of delivering gender-responsive services (Boppre, 2019) and evidence suggests attending to them can improve outcomes (Roddy et al, 2022; Williams et al, 2020).…”
Section: Gender-specific Needs and Gender-responsive Approachesmentioning
confidence: 99%